Environmental Impact Study through Physico- Chemical and Ichthyofaunal Diversity Analysis in Selected Major Rivers of Barpeta District, Assam - Hussain, Amin; Nag, Sudipta; Ahmed, Syed Rizaul Karim; Sarma, Kangkan Jyoti; Das, Aditya; Hasan, Rubaiya (Asian Journal of Biological and Life Sciences, 2024)
The present survey was made to study fish diversity and some of the important physico-chemical parameters in the four major rivers passing through Barpeta district, Assam-Chaulkhowa, Palla, Brahmaputra and Beki during the year 2018–2019 at three seasonal intervals. As per the water quality standards, the ph and temperature of the water at all the river locations were found to be stable. The concentrations of arsenic, iron, nitrate and copper in all four rivers were fairly stable. Other nutrients such as calcium showed remarkable variations. The organic matter level was very low during monsoon and high in summer. The fish diversity in accordance with the analysis of the water samples were found to productive, as the total fish species found were 24 in which the most abundant species have found in four rivers was Puntius sophore followed by Cirrhinus mrigala, while the least abundant species Hilsa ilisa (except Brahmaputra River), Chitala chitala and Nandus nandus were rare species in these rivers.
Keywords: Assam; Barpeta; Fish diversity; Water quality